Where Do Women With Urinary Incontinence Find Information About Absorbent Products and How Useful Do They Find It?. Issue 1 (January 2019) - Smith, Nicholas; Hunter, Kathleen F.; Rajabali, Saima; Milsom, Ian; Wagg, Adrian
Abstract : PURPOSE: This study aimed to determine from what sources women with urinary and dual urinary and fecal incontinence sought and received information about incontinence and absorbent products. We also evaluated source utility. DESIGN: Descriptive, embedded, mixed-methods study with qualitative interviews nested into a survey design in a modified explanatory sequence. SUBJECTS AND SETTING: The target population was community-dwelling women in Canada who used containment products to manage urinary incontinence. Three hundred fifteen women completed the online survey, and 9 participated in interviews. METHOD: Quantitative data were collected using an online survey that was advertised in multiple locations, including continence and urogynecology clinics, non-for-profit health Web sites, and social media. Descriptive statistics were used for analysis. Using initial quantitative data results, a semistructured interview guide was designed to gain further insight. Local survey participants were invited to interviews at the end of the survey. Interview transcripts were coded using content analysis. The codes were then collapsed into categories and finally themes. RESULTS: The most common sources of information (n = 284/315) were retail outlets (43%) and television/radio (42%). The greatest percentages of "useful" or "very useful" resources were healthcare professionals (83%). Content analysis identified 5 themes: (1) using existing knowledge, (2) seeking knowledge, (3) finding the right pad, (4) being safe and secure, and (5) perceptions of healthcare professionals' roles. Product choice was made through trial and error; women drew information from a variety of sources, including product labels. Perceptions of helpfulness of experiences with healthcare professionals varied. CONCLUSION: Although women used multiple sources when selecting containment products, they did not receive information in a manner that suited their needs, resulting in a trial-and-error approach to product selection. Healthcare professionals should actively give information on containment products during their assessment of continence in patient encounters.